Peranan Dewan Pengawas Syariah terhadap Praktik Kepatuhan Syariah dalam Perbankan Syariah di Indonesia - Bagya Agung Prabowo; Jasri Bin Jamal (Fakultas Hukum Universitas Islam Indonesia, 2017)
This research is to analyze the role of DPS (Dewan Pengawas Syariah or Sharia Supervisory Board) towards the practice of sharia obedience with the perspective of customer protection in sharia banking in Indonesia. This research adopted the analysis method based upon the doctrinal content by applying four types of legal approach including: (i) history; (ii) Fiqh/philosophy; (iii) comparison and (iv) analysis and critical. In addition, the approach alignment is also needed for the legislative alignment with Islamic philosophy and customer protection philosophy. The result of the research concluded that any violation in sharia obedience neglected by DPS will negatively impact the image and credibility of sharia banking to public; thus, it can bring an impact on the public trust. For this reason, the roles of DPS in sharia banking needs to be optimized, for instance related to the qualification of DPS appointment must be tighter and the support to its roles must be realized in sharia banking. DSN MUI as an institution issuing the fatwa (binding ruling) can make the coordination and equalize the perception with the DPS posted in sharia banks in Indonesia in supervising the operation of sharia bank to make it really playing a role and ready to run its task as the DPS.